Application of new serological (Major Membrane Protein II) enzyme linked immunosorbent assay for leprosy patients in Myanmar - Khin, Nwe Oo; Mi Htwe, Mi; Khine Zar, Win; Khin Thet, Wai; Kyaw, Myint; Kyaw, Kyaw (2009)
As serodiagnosis is the easiest way of diagnosing a disease, the utility of (Major Membrane Protein II) MMP-II antigen in the serodiagnosis of leprosy was examined and compared with NTP-BSA ELISA test. It was carried out on the blood samples of new leprosy cases and their contacts from Nyaungdon Township, and on new adult pulmonary TB cases of Yangon TB Center and childhood TB cases of Yangon Children's Hospital and North Okkalapa General Hospital between November 2006 and December 2007. The sensitivity of the tests on detecting leprosy patients who had not been treated was 58/77 (75.32%) and 54/77 (70.1%) for MB patients using MMP-II and NTP-BSA ELISA tests, respectively. It was 48/64 (75.0%) and 40/64 (62.50%) for PB patients using MMP-II and NTP-BSA ELISA tests, respectively. The sensitivity of MMP-II ELISA test was higher than that of NTP-BSA ELISA test on both leprosy patients. The sensitivity of MMP-II ELISA test was also higher than that of NTP-BSA ELISA test on TB patients in our study. Therefore, our data indicate that MMP-II ELISA could be useful as a supporting serodiagnostic tool in diagnosis of leprosy and childhood tuberculosis